Investigating the Effect of Different Implant Abutments on the Optical Properties of Monolithic Zirconia Crowns with High and Low Translucency and Different Thicknesses after Cementing with Temporary Cement - Fathi, Amirhossein; Nadian, Farshad; Nosouhian, Saeed; Mosharraf, Ramin; Khodadadi, Reza (European Dental Research and Biomaterials Journal, 2025)
Various factors affect the esthetics, color, and optical properties of implants. Among these factors, we can refer to the type of abutment, the thickness of the crown, and translucency.Two types of zirconia and titanium abutments with the same shape were placed on two regular-sized Bego bone-level fixtures. A total of 48 crowns including 12 monolithic zirconia crowns with high translucency and 12 with low translucency in two thicknesses of 0.4 and 0.8 mm for the titanium abutment and 12 monolithic zirconia crowns with high translucency and 12 with low translucency in two thicknesses of 0.4 and 0.8 mm for the zirconia abutment were made and then were bonded by temporary cement based on zinc oxide (Kerr temp-bond) on the existing abutments and then subjected to visual inspection.The color differences of the crowns in the titanium abutment group in both white and black backgrounds were significantly higher than in the zirconia abutment group (p <0.0001). After the intervention, the average translucency in the zirconia abutment group with high translucency at a thickness of 0.8 mm was the highest compared to other groups (p <0.05). In the zirconia abutment group on a black background with a thickness of 0.8 mm, the color difference of the crown with an average of 0.84 ± 0.46 was significantly lower than that of the 0.4 mm thickness with an average of 1.22 ± 0.22 (p = 0.018), but this difference was not significant in the titanium group.The translucency of titanium abutments, regardless of the thickness and color, was higher than that of zirconia before cement. However, after cement, the translucency of zirconia generally increased. Titanium abutments before and after cementing the crowns showed greater color differences than zirconia abutments. An increase in thickness in both groups reduced the color difference.
Keywords: implant crown; monolithic zirconia; color; translucency; cement